Arsenal of Defense : Fort Worth's Miltary Legacy - Pate, J'Nell L. (Book collections on Project MUSE., 2011)
Named after Mexican War general William Jenkins Worth, Fort Worth began as a military post in 1849. More than a century and a half later, the defense industry remains Fort Worth's major strength with Lockheed Martin's F-35s and Bell Helicopter's Ospreys flying the skies over the city. Arsenal of Defense: Fort Worth's Military Legacy covers the entire military history of Fort Worth from the 1840s with tiny Bird's Fort to the massive defense plants of the first decade of the twenty-first century. Although the city is popularly known as "Cowtown" for its iconic cattle drives and stockyards, soldie.